Relationship between the Obligations from the European Convention on Human Rights and the Accession to the European Union - Harun Halilović (Sriwijaya Law Review, 2023)
Bosnia and Herzegovina (B&H) has difficulty integrating and moving closer to the goal of becoming a member of the European Union (EU). From the legal perspective, the main issue is the need to fulfil the accession criteria. The article aims to examine the relationship between the obligations under the European Convention on Human Rights and Basic Freedoms (ECHR) and the obligations related to the European Union (EU) accession process, with emphasis on Bosnia and Herzegovina (B&H) as an EU membership candidate country. At first sight, those two obligations are separate. However, upon close examination, a strong link between those two obligations can be established using normative research with a historical approach, statute and case-based approach. On the other hand, the constitutional system of B&H has been described as discriminatory by numerous judgments of the European Court of Human Rights (ECtHR) and, most prominently, by the Sejdic-Finci case. B&H has difficulties implementing those judgments. Implementing those judgments is also set as one of the requirements of EU accession. Even if the two obligations seem separate at first sight, the ECHR has a special position within the law of the EU and is especially important in the accession of new Member States, including B&H. The research results show a special position of the ECHR in EU law and a link between the obligations under the ECHR and EU accession.